Generation Z Resilience in a Hybrid Work Landscape: A Phenomenological Study on Creative Industry Employees in Indonesia - Haryanti, Haryanti; Suratman, Maman; Suganda, Dadang; Hendri, Meriza (International Journal of Social Science and Business, 2025)
The transformation of work systems in the post-COVID-19 era has accelerated the widespread adoption of hybrid work models, including within the creative industry sector. While this model offers flexibility, it also presents new psychosocial challenges, particularly for Generation Z, who now dominate the younger workforce demographic. This study aims to explore the subjective experiences of Generation Z in cultivating resilience amid the dynamics of hybrid work. Employing an Interpretative Phenomenological Analysis (IPA) approach, in-depth interviews were conducted with eight Gen Z employees in creative roles to understand the adaptive strategies they had developed. The analysis revealed five core themes: (1) initial ambiguity and adaptation to hybrid reality, (2) the search for meaning and personal–professional balance, (3) the strength of social connections and emotional support, (4) the ambivalence of digital technology, and (5) self-reflection as a recovery mechanism. The findings suggest that resilience among Generation Z is not merely about endurance, but involves an active process of meaning-making and psychological growth that is reflective, social, and contextually grounded. Practical implications highlight the importance of organizational interventions that support emotional well-being, social inclusivity, and digital literacy as integral to strengthening the psychological capital of young employees in the hybrid work era.